Analisis Kualitas Instrumen Pemahaman Konsep pada Materi Energi Terbarukan Menggunakan Model Rasch - Rapi Alwi Azhar; Parlindungan Sinaga; Agus Danawan; Lina Aviyanti; Mohd Khairul Nizam Syah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to analyze the quality of a conceptual understanding test instrument on renewable energy using the Rasch measurement model. The instrument consisted of 19 multiple-choice items developed based on the conceptual understanding dimensions proposed by Anderson and Krathwohl (2001) and was administered to 75 tenth-grade senior high school students. Data were analyzed using MINISTEP version 5.10.3.0, including content validity (Aiken’s V coefficient), construct validity (unidimensionality, outfit MNSQ, ZSTD, and Point Measure Correlation), reliability, item difficulty, Differential Item Functioning (DIF), and the Wright Map. The results showed that 14 of the 19 items were content valid (V ≥ 0.80). The raw variance explained by measures was 36.5%, indicating that the instrument satisfied the unidimensionality assumption. The analysis also revealed a person reliability of 0.71 (acceptable), an item reliability of 0.94 (very good), and a Cronbach’s alpha (KR-20) of 0.77 (very good). Three items (S7, S10, and S19) exhibited significant Differential Item Functioning (DIF) based on gender. The Wright Map indicated that the mean student ability was 1.14 logits, while item difficulty ranged from −2.15 to 3.33 logits. Overall, the instrument was considered suitable for measuring students’ conceptual understanding of renewable energy after revisions were made to the problematic items.